A novel composite PCM for seasonal thermal energy storage of solar water heating system. (December 2020) - Wu, Wei; Wang, Xiaoyu; Xia, Man; Dou, Yiping; Yin, Zhengyu; Wang, Jun; Lu, Ping
Abstract: This paper presents a novel composite phase change material (PCM) with two phase transition temperatures (PTTs), which can be used in solar water heating system (SWHS) to accomplish the demand for seasonal thermal energy storage. A three-dimensional (3D) numerical model of evacuated tube collector (ETC) is established. An outdoor test rig has been fabricated to validate the numerical analysis. Differential scanning calorimetry (DSC) is employed to measure the thermal properties of PCMs. The numerical analysis shows that the natural convection effect cannot be ignored. The temperature gradients calculated in the axial direction during the solid sensible heating and phase change periods are respectively 0.02% and 1.7% of that in the radial direction in summer, 0.1% and 1% in winter, which indicates that the heat transfer is essentially in a two-dimensional (2D) way in these two periods. The DSC test illustrates that the enthalpy and PTT of the composite PCM are mainly affected by the component of single PCM with high PTT. Both the test and simulation show that CA/62, the combination of capric acid (CA) and #62 paraffin, can reach two quite different PTTs, to make it a suitable one in terms of seasonal thermal energy storage in SWHS. Highlights: A novel composite PCM with two PTTs is proposed, studied and evaluated by simulation and experiment. By using this composite PCM, SWHS can fulfill demand for seasonal thermal energy storage. Convection cannot be ignored during phase change and liquid sensible heating stages. Heat transfer during solid sensible heating and phase change stages is essentially in a 2D way. CA/62 is demonstrated as the most suitable composite PCM for SWHS with heat pump.